2015
DOI: 10.1080/10962247.2015.1033067
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between daily cardiovascular mortality and daily ambient concentrations of particulate pollutants (sulfur, arsenic, selenium, and mercury) and daily source contributions from coal power plants and smelters (individually, combined, and with interaction) in Phoenix, AZ, 1995–1998: A multipollutant approach to acute, time-series air pollution epidemiology: I

Abstract: The relationship between daily cardiovascular mortality and daily ambient concentrations of particulate pollutants (sulfur, arsenic, selenium, and mercury) and daily source contributions from coal power plants and smelters (individually, combined, and with interaction) in Phoenix, AZ, 1995-1998: A multipollutant approach to acute, time-series air pollution epidemiology: I William E. WilsonTo cite this article: William E. Wilson (2015) The relationship between daily cardiovascular mortality and daily ambient c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Dawd Gashu et al found that selenium de ciency may affect thyroid function [31]. Selenium is involved in the formation of the strong antioxidant enzyme glutathione peroxidase, which scavenges lipid peroxides in the body, binds to low-density lipoprotein and very low-density lipoprotein, alleviates hypercholesterolemia and hypertriglyceridemia, regulates blood lipids, and reduces blood viscosity [32]. Selenium and selenoproteins affects the maintenance of redox balance and normal function of endothelial cells [33].…”
Section: The Characteristics Of Selenium In Thementioning
confidence: 99%
“…Dawd Gashu et al found that selenium de ciency may affect thyroid function [31]. Selenium is involved in the formation of the strong antioxidant enzyme glutathione peroxidase, which scavenges lipid peroxides in the body, binds to low-density lipoprotein and very low-density lipoprotein, alleviates hypercholesterolemia and hypertriglyceridemia, regulates blood lipids, and reduces blood viscosity [32]. Selenium and selenoproteins affects the maintenance of redox balance and normal function of endothelial cells [33].…”
Section: The Characteristics Of Selenium In Thementioning
confidence: 99%
“…Furthermore, zinc has been shown to act as an anti-oxidant and to be involved in membrane stabilization suggesting a role in prevention of free radical-induced damaging especially during inflammatory processes 52 . Additionally, it is known that many environmental stressors such as pollution can lead to a chronic immune response dysregulation especially affected during development [53][54][55][56][57] . Underlying affected mechanisms induced by the described factors could be DNA methylation, which control key aspects of immune responses regulating peripheral immune system effector cell development, in which especially DNMT1 and DNMT3b seem to play a major role specially during development 58 .…”
Section: Suggestions Of Underlying Mechanismsmentioning
confidence: 99%